MR imaging-based risk stratification scoring system to predict clinical outcomes in carotid body tumors - Mahajan, Abhishek; Shaikh, Atif; Shukla, Shreya; Vaish, Richa; Agarwal, Ujjwal; Smriti, Vasundhara; Rastogi, Shivam; Deokar, Shonal; Suryavanshi, Shubham; Chaturvedi, Pankaj; Laskar, Sarbani Ghosh; Prabhash, Kumar; et al. (Frontiers in Oncology, 2024)
Objectives: To evaluate the role of pre-therapy MRI in predicting outcomes in carotid body tumors and proposal of a grading system for high and low-risk characteristics.: A retrospective observational study of 44 patients with 51 lesions from 2005-2020 was done. MR images were reviewed for carotid body tumor characteristics and a score was given which was correlated with intra and post-operative findings. The present modified classifications and our proposed Mahajan classification were compared with Shamblin's classification. The area under the curve and ROC curves were used to present the accuracy of different predictive models.Results: Our scoring system allotted a score of 0 to 15 on the basis of MRI characteristics with scores calculated for patients in our study ranging from 0 to 13. Lesions with scores of 0-6 were considered as low risk (45%) and scores of 7-15 were regarded as high risk for surgery (55%). The Mahajan classification staged tumor into 4 grades -I (10%), II (20%), IIIa (8%) and IIIb (62%).The frequency of vascular injury was 50% in Category I and 64% in category IIIb. The frequency of cranial nerve injury was 50%, 66% and 27% in category I, II and IIIb Conclusion: Mahajan classification of CBTs evaluates high-risk factors like the distance of tumor from skull base and angle of contact with ICA which forms the major predictors of neurovascular damage and morbidity associated with its surgery. Though Shamblin classification of CBT is the most widely accepted classification, our proposed Mahajan classification system provides an imaging-based alternative to prognosticate surgical candidates pre-operatively.